2015
DOI: 10.1016/j.jprot.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Discovery by proteogenomics and characterization of an RF-amide neuropeptide from cone snail venom

Abstract: In this study, a proteogenomic annotation strategy was used to identify a novel bioactive peptide from the venom of the predatory marine snail Conus victoriae. The peptide, conorfamide-Vc1 (CNF-Vc1), defines a new gene family. The encoded mature peptide was unusual for conotoxins in that it was cysteine-free and, despite low overall sequence similarity, contained two short motifs common to known neuropeptides/hormones. One of these was the C-terminal RF-amide motif, commonly observed in neuropeptides from a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 40 publications
1
42
0
1
Order By: Relevance
“…Mass spectrometry was performed as described previously (Robinson et al, 2015). Briefly, 0.5 μg of each venom sample was centrifuged at 13,000 x g for 10 min and loaded onto a microfluidic trap column packed with ChromXP C18-CL 3 μm particles (300 Å nominal pore size; equilibrated in 0.1% formic acid/5 % MeCN) at 5 μL/min using an Eksigent NanoUltra cHiPLC system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry was performed as described previously (Robinson et al, 2015). Briefly, 0.5 μg of each venom sample was centrifuged at 13,000 x g for 10 min and loaded onto a microfluidic trap column packed with ChromXP C18-CL 3 μm particles (300 Å nominal pore size; equilibrated in 0.1% formic acid/5 % MeCN) at 5 μL/min using an Eksigent NanoUltra cHiPLC system.…”
Section: Methodsmentioning
confidence: 99%
“…Examples include the conopressins (vasopressin analogues) from Conus geographus and Conus striatus (Cruz et al, 1987), contulakin-G (a neurotensin analogue) from C. geographus (Craig et al, 1999), RFamide neuropeptides from Conus spurius and Conus victoriae (Maillo et al, 2002; Robinson et al, 2015), conomap (a myoactive tetradecapeptide) from Conus vitulinus (Dutertre et al, 2006), conoCAPs (analogues of crustacean cardioactive peptide) from Conus villepinii (Möller et al, 2010) and neuropeptide-F/Y from Conus betulinus (Wu et al, 2010). Furthermore, we recently demonstrated that specialised insulins are an abundant and active component of some Conus venoms (Safavi-Hemami et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This approach rarely provides the identification of the full toxin sequences, even with a fully accurate genomic database. Still, it is sufficient to match MS data to associate chromatographic peaks or gel spots to identify a family of toxins, providing the opportunity to Later studies have demonstrated an additional utility of combining proteomic and genomic analyses: while traditionally proteomic analyses followed the process of genomic data generation and library assembly, combining proteomics and genomics in the process of genome/transcriptome assembly, or proteogenomics, allows the identification and annotation of novel unidentified proteins [133,134], as well as improved genomic sequence assembly [135]. Fig.…”
Section: Venomics and Mass Spectrometrymentioning
confidence: 99%
“…CNF-Sr2 also produces hyperactivity when injected intracranially into mice and demonstrated other symptoms such as paralysis in snails and limpet [46]. A third conorfamide, Vc1 from C. victoriae, showed bioactivity upon injection in mice and calcium imaging of mouse dorsal root ganglion cells revealed that the peptide elicits an increase in intracellular calcium levels [47]. …”
Section: Conorfamidesmentioning
confidence: 99%